Non-noble metal catalyst, preparation method and application
By using a combination of aluminum sol with cordierite support and copper lanthanum salt in non-precious metal catalysts, a loose porous structure and composite oxide are formed, which solves the problems of poor activity of non-precious metal catalysts at low temperatures and adsorption of water molecules, and achieves efficient VOCs degradation and anti-aging effects.
Patent Information
- Application Number
- CN202411277730.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
The existing non-precious metal catalysts have poor activity at low temperatures, easy to fall off and block the carrier pores, and more easily adsorb water molecules with greater polarity, resulting in a decrease in catalyst activity or even inactivation.
Aluminum sol and cordierite support are combined to form a loose porous structure through calcination treatment, and copper and lanthanum salts are combined as active components. The catalytic degradation is carried out using the Mars-van-Krevelen mechanism, and uniform dispersion and complex are promoted through active additive precursors. Oxide formation improves oxygen storage capacity and anti-aging ability.
It significantly improves the low-temperature catalytic oxidation activity of the catalyst, avoids the fall of active components, reduces the adsorption of water molecules with higher polarity, extends the service life of the catalyst, and improves the anti-aging ability.
Smart Images

Figure CN119140103A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic treatment of volatile organic compounds, and in particular to a non-precious metal catalyst, a preparation method and an application thereof. Background Art
[0002] Volatile organic compounds (abbreviated as VOCs) generally refer to organic compounds with a boiling point below 250°C at an atmospheric pressure of 101.325 kPa. VOCs are not only important precursors of ozone and secondary organic aerosols, but some VOCs also have an impact on human health and even have a carcinogenic risk. Therefore, it is of great significance to reduce the emission of VOCs.
[0003] At present, the technologies used for VOCs emission reduction and control include a variety of recovery technologies (such as adsorption, absorption, membrane separation and condensation, etc.) and oxidation technologies (such as catalytic oxidation, biodegradation, photocatalytic degradation and plasma degradation, etc.). However, most recovery technologies have defects such as high cost, low removal rate and long reaction cycle. Among the oxidation technologies, catalytic oxidation has attracted widespread attention in the application of VOCs emission reduction and control due to its high activity, simple catalyst preparation and low cost.
[0004] The catalysts commonly used for VOCs catalytic oxidation are divided into two categories: precious metal catalysts and non-precious metal catalysts. Precious metal catalysts have superior catalytic activity, but they are expensive. Non-precious metal catalysts are low-cost, but have poor low-temperature activity. In addition, the surface active components of non-precious metal catalysts are easy to fall off and block the pores on the carrier, which, on the one hand, reduces the activity of non-precious metal catalysts, and on the other hand, makes it difficult for VOCs gas to circulate, and the pressure in the reactor increases, causing safety hazards. In addition, in industrial tail gas, in addition to VOCs, there are interfering components such as water molecules. Water molecules will compete with VOCs for adsorption and reaction at the catalytic reaction site, which will lead to a decrease in catalyst activity or even deactivation. Specifically, when water molecules and VOCs molecules coexist in the gas phase, the catalyst will preferentially adsorb water molecules with greater polarity, with a large adsorption amount of water molecules and a small adsorption amount of VOCs molecules, resulting in a slowdown in the catalytic oxidation reaction rate of VOCs and a decrease in activity. In addition, if a chemical reaction occurs between water molecules and the catalyst, they will be tightly bound to the active site after adsorption and cannot be desorbed from the system, resulting in catalyst deactivation.
[0005] In summary, there is a need to provide a non-precious metal catalyst, a preparation method and an application to solve the problems of poor low-temperature activity of existing non-precious metal catalysts, easy shedding of surface active components to block the pores of the carrier, and easier adsorption of water molecules with greater polarity, resulting in decreased catalyst activity or even deactivation. Summary of the invention
[0006] The present invention aims to provide a non-precious metal catalyst, a preparation method and an application thereof. The specific technical scheme is as follows:
[0007] In a first aspect, the present invention provides a method for preparing a non-precious metal catalyst, comprising:
[0008] The cordierite carrier is immersed in aluminum sol, taken out after the immersion, and subjected to a first calcination treatment in an air atmosphere to obtain a composite carrier;
[0009] The impregnation solution is prepared by adding an active component precursor salt into a solvent, and dissolving and mixing the active component precursor salt to obtain an impregnation solution; the active component precursor salt includes a copper salt and a lanthanum salt, and the molar ratio of copper to lanthanum is 3:1-15:1; the solvent includes an organic solvent or a mixture of an organic solvent and water;
[0010] The composite carrier is placed in the impregnation solution and impregnated, and then subjected to a second calcination treatment in an air atmosphere to obtain a non-precious metal catalyst.
[0011] Optionally, the first calcination treatment is performed at a temperature of 300-600° C. and for a time of 1-3 h.
[0012] Optionally, the second calcination treatment is performed at a temperature of 250-700° C. and for a time of 5-8 h.
[0013] Optionally, in the preparation of the impregnation solution, the mass ratio of the active component precursor salt to the solvent is 1:1-1:5; the impregnation time used in the impregnation treatment is 2-8 minutes, and the impregnation temperature is 20-25°C.
[0014] Optionally, the organic solvent includes at least one of acetone and anhydrous ethanol.
[0015] Optionally, in the prepared non-precious metal catalyst, the loading amount of the active component is 5wt%-20wt%; the active component includes copper and lanthanum.
[0016] Optionally, when preparing the impregnation solution, an active agent precursor salt is also included; the mass ratio of the active agent precursor salt to the active component precursor salt is 0-1:5; the active agent precursor salt and the active component precursor salt are added to the solvent, and the impregnation solution is obtained after dissolution and mixing.
[0017] Optionally, the active agent precursor salt includes at least one of a cobalt salt, a yttrium salt, an iron salt, a zinc salt and a zirconium salt;
[0018] The loading amount of the aluminum sol on the cordierite carrier is 2 wt % to 8 wt %.
[0019] In a second aspect, the present invention provides a non-precious metal catalyst prepared by the method for preparing the non-precious metal catalyst.
[0020] In a third aspect, the present invention provides a use of the non-precious metal catalyst in catalytic degradation of volatile organic compounds.
[0021] The application of the technical solution of the present invention has at least the following beneficial effects:
[0022] (1) The present invention provides a non-precious metal catalyst, preparation method and application. After the first calcination treatment of aluminum sol, a loose porous structure of Al2O3 is formed on the surface of cordierite, which greatly increases the specific surface area of the composite carrier, provides a good adhesion environment for the subsequent active components, and makes the loaded active components not easy to fall off; at the same time, the loose porous structure of the composite carrier is also convenient for adsorbing more VOCs, so that VOCs and active components are fully contacted; the use of active component precursor salt can make the prepared non-precious metal catalyst have active components of copper and lanthanum, wherein copper contains multiple valence states, such as Cu + and Cu 2+ ; Lanthanum contains various valence states, such as La 3+ and La 4+ ; The Mars-van-Krevelen (abbreviated as Mvk) mechanism is followed in the catalytic degradation of VOCs, that is, VOCs react with the lattice oxygen in the non-precious metal catalyst; The Mvk mechanism is mainly divided into two steps: 1) VOCs that diffuse into and are adsorbed on the surface of the non-precious metal catalyst combine with the lattice oxygen on the surface of the non-precious metal catalyst and are oxidized to CO2 and H2O; At the same time, oxygen vacancies are generated on the surface of the non-precious metal catalyst and are reduced; 2) The non-precious metal catalyst is oxidized by oxygen in the gas phase; In the process of reduction and oxidation of oxygen holes on the surface of the non-precious metal catalyst, copper and lanthanum in a specific molar ratio of multiple valence states are continuously reduced and oxidized to ensure efficient degradation of VOCs. In addition, non-precious metal catalysts can provide acidic sites to adsorb and activate VOCs; Specifically, the copper cations and lanthanum cations exposed on the surface of the non-precious metal catalyst are typical Lewis acids, which promote the severance of CH bonds; The hydroxyl groups on the surface of the non-precious metal catalyst are typical acid, and Acids can provide H + To activate VOCs, making it easier for them to participate in the reaction; the present invention uses the synergistic effect of the acidic sites on the surface of the non-precious metal catalyst and the multivalent specific molar ratio of copper and lanthanum to enable the non-precious metal catalyst to have excellent low-temperature catalytic oxidation activity. The solvent used in the present invention can ensure that the copper salt and lanthanum salt are fully dissolved, and increase the viscosity of the impregnation solution, so that the active components are more firmly loaded on the composite carrier; if only water is used as the solvent, the active components are easy to fall off after being loaded on the composite carrier.
[0023] (2) The present invention adopts an active promoter precursor salt, which can promote the uniform dispersion of active components and avoid agglomeration of active components; the active promoter precursor salt can react with the active components in the non-precious metal catalyst to produce a composite oxide, and the composite oxide has more lattice oxygen or active sites than the single-component oxide; in addition, the active promoter precursor salt can promote the formation and migration of oxygen vacancies in the non-precious metal catalyst to increase the oxygen storage capacity of the non-precious metal catalyst. When the oxygen storage capacity of the non-precious metal catalyst is improved, there is more abundant lattice oxygen on the surface of the non-precious metal catalyst to participate in the oxidation of VOCs, thereby improving the catalytic performance.
[0024] (3) The present invention uses an active promoter precursor salt to improve the anti-aging ability of non-precious metal catalysts. Specifically, 1) Stabilize the structure of non-precious metal catalysts: The active promoter precursor salt forms a stable composite oxide with the active components in the non-precious metal catalyst to prevent the non-precious metal catalyst from undergoing structural changes or deactivation during high temperature or long-term use, thereby enhancing the structural stability of the non-precious metal catalyst; 2) Inhibit carbon deposition: The active promoter precursor salt is used to adsorb or convert carbon deposition precursor substances to reduce the formation of carbon deposition, thereby extending the service life of the non-precious metal catalyst; 3) Promote the formation and migration of oxygen vacancies: The active promoter precursor salt is used to promote the formation and migration of oxygen vacancies, thereby enhancing the oxygen storage capacity of the non-precious metal catalyst; the presence of oxygen vacancies helps Recycling of non-precious metal catalysts in redox reactions reduces catalyst aging; 4) Regulating the surface properties of non-precious metal catalysts: using active agent precursor salts to change the surface properties of non-precious metal catalysts, thereby improving the anti-aging ability of non-precious metal catalysts; specifically, such as changing the surface charge distribution of non-precious metal catalysts, and adjusting the interaction between metals and carriers (SMSI effect), thereby improving the stability of active sites and thus improving the anti-aging ability of non-precious metal catalysts; such as increasing the surface roughness of non-precious metal catalysts, which acts as a physical barrier to avoid sintering of active sites, thereby improving the anti-aging ability of non-precious metal catalysts.
[0025] (4) After being modified by acetone and anhydrous ethanol, the active adsorption sites on the non-precious metal catalyst prepared by the present invention tend to be non-polar adsorption sites, which are more likely to adsorb VOCs molecules with lower polarity in the gas phase rather than water molecules with higher polarity. Therefore, the present invention solves the problem that the existing non-precious metal catalysts are more likely to adsorb water molecules with higher polarity, resulting in decreased catalyst activity or even deactivation.
[0026] In addition to the above-described purposes, features and advantages, the present invention has other purposes, features and advantages. The present invention will be further described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0028] Figure 1 is a cross-sectional view of the non-precious metal catalyst prepared in Example 1 of the present invention;
[0029] Figure 2 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the newly prepared non-precious metal catalyst in Example 1;
[0030] Figure 3 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the aged non-precious metal catalyst in Example 1;
[0031] Figure 4 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the newly prepared non-precious metal catalyst in Example 2;
[0032] Figure 5 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the aged non-precious metal catalyst in Example 2;
[0033] Figure 6 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the newly prepared non-precious metal catalyst in Example 3;
[0034] Figure 7 This is a data graph of the degradation activity evaluation experiment of propylene by the newly prepared non-precious metal catalyst in Example 3;
[0035] Figure 8 This is a data chart of the degradation activity evaluation experiment of styrene by the newly prepared non-precious metal catalyst in Example 3;
[0036] Fig. 9 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the aged non-precious metal catalyst in Example 3;
[0037] Fig.10 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the newly prepared non-precious metal catalyst in Example 4;
[0038] Fig.11 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the aged non-precious metal catalyst in Example 4;
[0039] Fig.12 is a cross-sectional view of the non-precious metal catalyst prepared in Comparative Example 1;
[0040] Fig.13 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the newly prepared non-precious metal catalyst in Comparative Example 1;
[0041] Fig.14 This is a data graph of the degradation activity evaluation experiment of cyclohexane by the aged non-precious metal catalyst in Example 1;
[0042] Fig.15 is a cross-sectional view of the non-precious metal catalyst prepared in Comparative Example 2;
[0043] Fig.16 This is a data chart of an activity evaluation experiment of cyclohexane degradation using a commercial non-precious metal catalyst used in Comparative Example 3;
[0044] Fig.17 This is a data chart of the degradation activity evaluation experiment of cyclohexane using a commercial non-precious metal catalyst adopted in Example 4. DETAILED DESCRIPTION
[0045] The following will be combined with the accompanying drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0046] Embodiment 1:
[0047] A method for preparing a non-precious metal catalyst comprises:
[0048] The cordierite carrier is immersed in aluminum sol, taken out after immersion, and subjected to a first calcination treatment in a muffle furnace under air atmosphere to obtain a composite carrier; the temperature used in the first calcination treatment is 600°C and the time is 2h; the loading amount of the aluminum sol on the cordierite carrier is 5wt%.
[0049] An impregnation solution is prepared by adding an active component precursor salt into a solvent, and dissolving and mixing to obtain an impregnation solution; wherein the mass ratio of the active component precursor salt to the solvent is 1:1.5; the active component precursor salt includes a copper salt (specifically copper nitrate trihydrate) and a lanthanum salt (specifically lanthanum nitrate hexahydrate), and the molar ratio of copper to lanthanum is 6:1; and the solvent is an organic solvent, specifically a mixed solution of acetone and anhydrous ethanol in a volume ratio of 1:3;
[0050] After the composite carrier is placed in the impregnation solution and impregnated, it is subjected to a second calcination treatment in a muffle furnace under an air atmosphere to obtain a non-precious metal catalyst; the temperature used in the second calcination treatment is 300°C and the time is 6 hours; the impregnation treatment uses an impregnation time of 2 minutes and an impregnation temperature of 25°C.
[0051] In the prepared non-precious metal catalyst, the loading amount of the active component is 8wt%; the active components are copper and lanthanum; the loading amount of the active component represents the ratio of the mass of the active component to the mass of the composite carrier.
[0052] Figure 1 This is a cross-sectional view of the non-precious metal catalyst prepared in Example 1. The color of the non-precious metal catalyst is black.
[0053] 1) Experimental evaluation of the degradation activity of cyclohexane using the newly prepared non-precious metal catalyst in Example 1
[0054] First, the non-precious metal catalyst newly prepared in Example 1 was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 250°C; then, a mixed gas with a total flow rate of 80 mL / min was introduced; in the mixed gas, the cyclohexane concentration was 1500 ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the air velocity was 15000 h -1 The reaction temperature was set at 310°C, and the non-precious metal catalyst newly prepared in Example 1 was subjected to the same degradation activity evaluation experiment as the non-precious metal catalyst newly prepared in Example 1 at 250°C. The results are as follows Figure 2 As shown, the degradation rate of cyclohexane by the newly prepared non-precious metal catalyst in Example 1 is about 96% at 250°C and about 99% at 310°C, showing a very high degradation activity.
[0055] 2) Experimental evaluation of the degradation activity of cyclohexane by aged non-precious metal catalysts
[0056] The newly prepared non-precious metal catalyst of Example 1 was aged. Specifically, the newly prepared non-precious metal catalyst was aged at a temperature of 650° C., an O 2 volume content of 20%, a humidity of 10%, N 2 as a balance gas, and a space velocity of 10000 h -1 Aging in atmosphere for 48h.
[0057] The aged non-precious metal catalyst was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 310°C. Then, a mixed gas with a total flow rate of 80 mL / min was introduced, wherein the cyclohexane concentration was 1500 ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000 h -1 The reaction temperature was set at 400°C, and the aged non-precious metal catalyst was subjected to the same degradation activity evaluation experiment as the above-mentioned aged non-precious metal catalyst at 310°C. The results are as follows Figure 3As shown, compared with the newly prepared non-precious metal catalyst, the activity of the aged non-precious metal catalyst decreased slightly, the degradation rate of cyclohexane at 310°C was about 75%, and the degradation rate of cyclohexane at 400°C was about 99%, showing strong anti-aging ability.
[0058] Embodiment 2:
[0059] Different from Example 1, when preparing the non-precious metal catalyst, the molar ratio of copper to lanthanum is 8:1.
[0060] 1) Experimental evaluation of the degradation activity of cyclohexane using the newly prepared non-precious metal catalyst in Example 2
[0061] First, the newly prepared non-precious metal catalyst in Example 2 was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 250°C; then, a mixed gas with a total flow rate of 80 mL / min was introduced; in the mixed gas, the cyclohexane concentration was 1500 ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the air velocity was 15000 h -1 The reaction temperature was set at 310°C, and the non-precious metal catalyst newly prepared in Example 2 was subjected to the same degradation activity evaluation experiment as the non-precious metal catalyst newly prepared in Example 2 at 250°C. The results are as follows Figure 4 As shown, the degradation rate of cyclohexane for the newly prepared non-precious metal catalyst in Example 2 is about 97% at 250°C and about 99% at 310°C, showing a very high degradation activity.
[0062] 2) Experimental evaluation of the degradation activity of cyclohexane by aged non-precious metal catalysts
[0063] The newly prepared non-precious metal catalyst of Example 2 was aged. Specifically, the newly prepared non-precious metal catalyst was aged at a temperature of 650° C., an O 2 volume content of 20%, a humidity of 10%, N 2 as a balance gas, and a space velocity of 10000 h -1 Aging in atmosphere for 48h.
[0064] The aged non-precious metal catalyst was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 310°C. Then, a mixed gas with a total flow rate of 80 mL / min was introduced, wherein the cyclohexane concentration was 1500 ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000 h -1 The reaction temperature was set at 400°C, and the aged non-precious metal catalyst was subjected to the same degradation activity evaluation experiment as the above-mentioned aged non-precious metal catalyst at 310°C. The results are as follows Figure 5As shown, compared with the newly prepared non-precious metal catalyst, the activity of the aged non-precious metal catalyst decreased slightly, the degradation rate of cyclohexane at 310°C was about 70%, and the degradation rate of cyclohexane at 400°C was about 99%, showing strong anti-aging ability.
[0065] Embodiment 3:
[0066] The same preparation method of the non-precious metal catalyst as in Example 1 was adopted.
[0067] 1) Experimental evaluation of the degradation activity of cyclohexane using the newly prepared non-precious metal catalyst in Example 3
[0068] First, the newly prepared non-precious metal catalyst in Example 3 was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 250°C; then, a mixed gas with a total flow rate of 1500mL / min was introduced; in the mixed gas, the cyclohexane concentration was 500ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000h -1 The reaction temperature was set at 310°C, and the non-precious metal catalyst newly prepared in Example 3 was subjected to the same degradation activity evaluation experiment as the non-precious metal catalyst newly prepared in Example 3 at 250°C. The results are as follows Figure 6 As shown, the degradation rate of the newly prepared non-precious metal catalyst in Example 3 for cyclohexane is about 94% at 250°C and about 99% at 310°C, showing a very high degradation activity.
[0069] 2) Experimental evaluation of propylene degradation activity using the newly prepared non-precious metal catalyst in Example 3
[0070] First, the newly prepared non-precious metal catalyst in Example 3 was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 200°C; then, a mixed gas with a total flow rate of 1500mL / min was introduced; in the mixed gas, the propylene concentration was 940ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000h -1 The reaction temperature was set at 235°C, and the non-precious metal catalyst newly prepared in Example 3 was subjected to the same degradation activity evaluation experiment as the non-precious metal catalyst newly prepared in Example 3 at 200°C. The results are as follows Figure 7 As shown, the degradation rate of propylene by the newly prepared non-precious metal catalyst in Example 3 is 14.1% at 200°C and 99.6% at 235°C, showing a very high degradation activity.
[0071] 3) Experimental evaluation of the degradation activity of styrene using the newly prepared non-precious metal catalyst in Example 3
[0072] First, the newly prepared non-precious metal catalyst in Example 3 was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 275°C; then, a mixed gas with a total flow rate of 1500mL / min was introduced; in the mixed gas, the styrene concentration was 940ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the air velocity was 15000h -1 The reaction temperature was set at 285°C, and the non-precious metal catalyst newly prepared in Example 3 was subjected to the same degradation activity evaluation experiment as the non-precious metal catalyst newly prepared in Example 3 at 275°C. The results are as follows Figure 8 As shown, the degradation rate of the newly prepared non-precious metal catalyst in Example 3 for styrene is 20.1% at 275°C and 99.9% at 285°C, showing a very high degradation activity.
[0073] 4) Experimental evaluation of the degradation activity of cyclohexane by aged non-precious metal catalysts
[0074] The newly prepared non-precious metal catalyst of Example 3 was aged. Specifically, the newly prepared non-precious metal catalyst was aged at a temperature of 650° C., an O 2 volume content of 20%, a humidity of 10%, N 2 as a balance gas, and a space velocity of 10000 h -1 Aging in atmosphere for 48h.
[0075] The aged non-precious metal catalyst was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 310°C. Then, a mixed gas with a total flow rate of 1500 mL / min was introduced, wherein the cyclohexane concentration was 500 ppm, the O2 volume content was 20%, the humidity was 10%, and N2 was used as the balance gas. The space velocity was 15000 h -1 The reaction temperature was set at 400°C, and the aged non-precious metal catalyst was subjected to the same degradation activity evaluation experiment as the above-mentioned aged non-precious metal catalyst at 310°C. The results are as follows Fig. 9 As shown, compared with the newly prepared non-precious metal catalyst, the activity of the aged non-precious metal catalyst decreased slightly, the degradation rate of cyclohexane at 310°C was about 58%, and the degradation rate of cyclohexane at 400°C was about 99%, showing strong anti-aging ability.
[0076] Embodiment 4:
[0077] On the basis of Example 1, an active agent precursor salt (specifically zirconium nitrate pentahydrate) is further added to the solvent; the mass ratio of the active agent precursor salt to the active component precursor salt is 0.5:5.
[0078] 1) Experimental evaluation of the degradation activity of cyclohexane using the newly prepared non-precious metal catalyst in Example 4
[0079] First, the newly prepared non-precious metal catalyst of Example 4 was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 250°C; then, a mixed gas with a total flow rate of 1500mL / min was introduced; in the mixed gas, the cyclohexane concentration was 500ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the air velocity was 15000h -1 The reaction temperature was set at 310°C, and the non-precious metal catalyst newly prepared in Example 4 was subjected to the same degradation activity evaluation experiment as the non-precious metal catalyst newly prepared in Example 4 at 250°C. The results are as follows Fig.10 As shown, the degradation rate of cyclohexane for the newly prepared non-precious metal catalyst in Example 4 is about 80% at 250°C and about 99% at 310°C, showing a very high degradation activity.
[0080] 2) Experimental evaluation of the degradation activity of cyclohexane by aged non-precious metal catalysts
[0081] The newly prepared non-precious metal catalyst of Example 4 was aged. Specifically, the newly prepared non-precious metal catalyst was aged at a temperature of 650° C., an O 2 volume content of 20%, a humidity of 10%, N 2 as a balance gas, and a space velocity of 10000 h -1 Aging in atmosphere for 48h.
[0082] The aged non-precious metal catalyst was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 310°C. Then, a mixed gas with a total flow rate of 1500 mL / min was introduced, wherein the cyclohexane concentration was 500 ppm, the O2 volume content was 20%, the humidity was 10%, and N2 was used as the balance gas. The space velocity was 15000 h -1 The reaction temperature was set at 400°C, and the aged non-precious metal catalyst was subjected to the same degradation activity evaluation experiment as the above-mentioned aged non-precious metal catalyst at 310°C. The results are as follows Fig.11 As shown, compared with the newly prepared non-precious metal catalyst, the activity of the aged non-precious metal catalyst decreased slightly, the degradation rate of cyclohexane at 310°C was about 68%, and the degradation rate of cyclohexane at 400°C was about 99%, showing strong anti-aging ability.
[0083] Compared with Example 3, the addition of the active agent precursor salt in Example 4 can improve the degradation rate of cyclohexane of the aged non-precious metal catalyst at 310° C., which indicates that the addition of the active agent precursor salt can improve the anti-aging ability of the non-precious metal catalyst.
[0084] Comparative Example 1:
[0085] Different from Example 1, water is used as the solvent, urea is added to the water, and the mass ratio of urea to water is 1:20.
[0086] Fig.12 It is a cross-sectional view of the non-precious metal catalyst prepared in Comparative Example 1. The color of the non-precious metal catalyst is black.
[0087] 1) Experimental evaluation of the degradation activity of cyclohexane using the newly prepared non-precious metal catalyst in Comparative Example 1
[0088] First, the non-precious metal catalyst newly prepared in Comparative Example 1 was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 250°C; then, a mixed gas with a total flow rate of 80 mL / min was introduced; in the mixed gas, the cyclohexane concentration was 1500 ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000 h -1 The reaction temperature was set at 310°C, and the non-precious metal catalyst newly prepared in Comparative Example 1 was subjected to the same degradation activity evaluation experiment as the non-precious metal catalyst newly prepared in Comparative Example 1 at 250°C. The results are as follows Fig.13 As shown, the degradation rate of cyclohexane by the newly prepared non-precious metal catalyst in Comparative Example 1 is about 43% at 250°C, and the degradation rate of cyclohexane by the newly prepared non-precious metal catalyst in Comparative Example 1 is about 99% at 310°C.
[0089] 2) Experimental evaluation of the degradation activity of cyclohexane by aged non-precious metal catalysts
[0090] The newly prepared non-precious metal catalyst of Comparative Example 1 was aged. Specifically, the newly prepared non-precious metal catalyst was aged at a temperature of 650° C., an O2 volume content of 20%, a humidity of 10%, N2 as a balance gas, and a space velocity of 10000 h -1 Aging in atmosphere for 48h.
[0091] The aged non-precious metal catalyst was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 310°C. Then, a mixed gas with a total flow rate of 80 mL / min was introduced, wherein the cyclohexane concentration was 1500 ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000 h -1 The reaction temperature was set at 400°C, and the aged non-precious metal catalyst was subjected to the same degradation activity evaluation experiment as the above-mentioned aged non-precious metal catalyst at 310°C. The results are as follows Fig.14 As shown, compared with the newly prepared non-precious metal catalyst, the activity of the aged non-precious metal catalyst decreases slightly, the degradation rate of cyclohexane is about 7.43% at 310°C, and the degradation rate of cyclohexane is about 85% at 400°C, and the anti-aging ability is poor.
[0092] Comparing the catalytic activities of Example 1 and Comparative Example 1, the degradation rate of cyclohexane of the non-precious metal catalyst prepared in Example 1 in both the fresh state and the aged state is higher than that of Comparative Example 1, indicating that the addition of organic solvents in the impregnation solution is beneficial to improving the firmness of the active component loading, catalytic activity and anti-aging ability.
[0093] Comparative Example 2:
[0094] Different from Example 1, when preparing the non-precious metal catalyst, the molar ratio of copper to lanthanum is 1:1.
[0095] Fig.15 It is a cross-sectional view of the non-precious metal catalyst prepared in Comparative Example 2. The color of the non-precious metal catalyst is black.
[0096] Comparative Example 3:
[0097] The catalyst used in Comparative Example 3 is a commercial Mn-based non-precious metal catalyst.
[0098] The commercial non-precious metal catalyst was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 250°C. Then, a mixed gas with a total flow rate of 1500mL / min was introduced. In the mixed gas, the cyclohexane concentration was 500ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000h -1 The reaction temperature was set at 310°C, and the commercial non-precious metal catalyst was subjected to the same degradation activity evaluation experiment as the commercial non-precious metal catalyst at 250°C. The results are as follows Fig.16 As shown, the degradation rate of cyclohexane by the commercial non-precious metal catalyst at 250°C is about 21%, and the degradation rate of cyclohexane at 310°C is about 70%.
[0099] Comparative Example 4:
[0100] The catalyst used in Comparative Example 4 is a commercial Cu-based non-precious metal catalyst.
[0101] The commercial non-precious metal catalyst was placed in a fixed bed reactor for degradation activity evaluation experiment, and the reaction temperature was 250°C. Then, a mixed gas with a total flow rate of 1500mL / min was introduced. In the mixed gas, the cyclohexane concentration was 500ppm, the O2 volume content was 20%, the humidity was 10%, N2 was used as the balance gas, and the space velocity was 15000h -1 The reaction temperature was set at 310°C, and the commercial non-precious metal catalyst was subjected to the same degradation activity evaluation experiment as the commercial non-precious metal catalyst at 250°C. The results are as follows Fig.17As shown, the degradation rate of cyclohexane by the commercial non-precious metal catalyst at 250°C is about 13%, and the degradation rate of cyclohexane at 310°C is about 75%.
[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a non-precious metal catalyst, It is characterized in that include: The cordierite carrier is immersed in aluminum sol, taken out after the immersion, and subjected to a first calcination treatment in an air atmosphere to obtain a composite carrier; The impregnation solution is prepared by adding an active component precursor salt into a solvent, and dissolving and mixing the active component precursor salt to obtain an impregnation solution; the active component precursor salt includes a copper salt and a lanthanum salt, and the molar ratio of copper to lanthanum is 3:1-15:1; the solvent includes an organic solvent or a mixture of an organic solvent and water; The composite carrier is placed in the impregnation solution and impregnated, and then subjected to a second calcination treatment in an air atmosphere to obtain a non-precious metal catalyst.
2. The method for preparing the non-precious metal catalyst according to claim 1, It is characterized in that The first calcination treatment is carried out at a temperature of 300-600° C. and for a time of 1-3 hours.
3. The method for preparing the non-precious metal catalyst according to claim 1, It is characterized in that The second calcination treatment is carried out at a temperature of 250-700° C. and for a time of 5-8 hours.
4. The method for preparing the non-precious metal catalyst according to claim 1, It is characterized in that In the preparation of the impregnation solution, the mass ratio of the active component precursor salt to the solvent is 1:1-1:5; the impregnation time used in the impregnation treatment is 2-8 minutes, and the impregnation temperature is 20-25°C.
5. The method for preparing the non-precious metal catalyst according to claim 1, It is characterized in that The organic solvent includes at least one of acetone and anhydrous ethanol.
6. The method for preparing the non-precious metal catalyst according to claim 1, It is characterized in that In the prepared non-precious metal catalyst, the loading amount of the active component is 5wt%-20wt%; the active component includes copper and lanthanum.
7. A method for preparing a non-precious metal catalyst according to any one of claims 1 to 6, It is characterized in that When preparing the impregnation solution, an active agent precursor salt is also included; the mass ratio of the active agent precursor salt to the active component precursor salt is 0-1:5; the active agent precursor salt and the active component precursor salt are added to the solvent, and the impregnation solution is obtained after dissolution and mixing.
8. The method for preparing the non-precious metal catalyst according to claim 7, It is characterized in that The active agent precursor salt includes at least one of a cobalt salt, a yttrium salt, an iron salt, a zinc salt and a zirconium salt; The loading amount of the aluminum sol on the cordierite carrier is 2 wt % to 8 wt %.
9. A non-precious metal catalyst, It is characterized in that The catalyst is prepared by the method for preparing a non-precious metal catalyst as claimed in claim 8.
10. Use of the non-precious metal catalyst as claimed in claim 9 in catalytic degradation of volatile organic compounds.
